PENGAMBILAN OLEORESIN DARI LIMBAH AMPAS JAHE INDUSTRI JAMU (PT. SIDO MUNCUL) DENGAN METODE EKSTRAKSI - Alyssa Nahla Amir; Puspita Firsty Lestari; Indro Sumantri (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2013)
Utilization of ginger pulp waste from herbal medicine industry in Indonesia currently used for making fertilizer and fuel, whereas the ginger pulp still contain high oleoresin. It is expected that the results of this study may utilize the ginger dregs of herbal medicine industry to be oleoresin products, suggest the appropriate extraction techniques, affecting operation variables and the optimum conditions for batch extraction of ginger oleoresins. This research used extraction method with various solvents in batch. Fixed variable used in this study is the weight of ginger 50 gr, volume of solvents 300 mL, extraction time 5.5 hour and stirring speed of 450 rpm. While the change variable is extraction temperature 30oC, 40oC, 50 oC and 60 oC and types of solvent (ethanol, n-Hexane and acetone). As the result from the research that the type of solvent and temperature variations affect oleoresin extracted. The optimum extraction conditions to produce a high yield of ginger oleoresin and good quality obtained in the combined treatment of ethanol solvent type, time of 5.5 hours and a temperature of 40oC with oleoresin concentration of 12.2%, 0.955 density (g/ ml) and a refractive index of 1.370.